Technological problems in the energy field in the developing countries : development of the technological capability of the petroleum industry in Peru (Geneva United Nations, 1984)
Technological problems in the energy field in the developing countries : development of the technological capability of the petroleum industry in Peru .
aia 29/03/2019
Loans
Keywords: Petroleum Industry; Petroleum Policy; Technology Industry; IndustrialDevelopment